Problematika pemanfaatan perpustakaan digital Pustabiblia bagi dosen IAIN Salatiga - Yenianti, Ifonilla (Daluang: Journal of Library and Information Science, 2022)
Introduction. The digital ebook library Pustabiblia is an ebook collection service application belonging to the IAIN Salatiga library that can be accessed by lecturers to support their information needs. This study aims to understand about the existence of Pustabiblia ebook services and the factor of the lack of access for lecturers to library ebooks owned by IAIN Salatiga.Methodology. This research uses a qualitative descriptive approach from the results of interview, observations and documentation. The informants of this research are FEBI lecturers who are members and are active members of the ebook Pustabiblia.Results and discussion. The results of this study indicate that FEBI lecturers are aware of the existence of ebook library services through librarians, WhatsApp group, website, and library social media. The factors for the lack of access to Pustabiblia services by FEBI lecturers are technical and non-technical factors. Technical factors are including alignment of collections with teaching/syllabic materials, system integration, internet network stability, internet quota limitations, storage capacity, application compatibility, and account footprint, while non-technical factors are the lack of socialization and promotion of the Pustabiblia ebook service, busy work, and not being the main source of reference.Conclusion. FEBI Lecturers have already known ebooks from various sources, but in accessing them there are still technical and non-technical obstacles, the lack of socialization and promotion which is the most dominant factor in all interview data. The recommendations are aligning ebooks with the needs of teaching materials, socializing, developing and integrating ebook applications, and intensively communicating with lecturers